Study on the Influence of Pile Installation Disturbance on the Settlement of Composite Foundation - Zhiwei Shao; Baoning Hong; Xin Liu; Yunlong Yao; Dongning Sun; Guisen Wang (Applied Sciences)
The disturbance generated during the pile installation process increased the compressibility of the soil between the piles, thereby causing additional settlement of the composite foundation. This study was conducted against the background of a highway soft foundation treatment project in Zhongshan. Before and after the installation of cement mixing piles (CMP) and pre-stressed high-strength concrete pipe pile (PHC), a piezocone penetration test (CPTU) was applied to assess the soil between the piles and quantify the disturbance. Based on this, the settlement of the composite foundation was predicted using the stress modified method and finite element method (FEM). The results indicate that under low embankment load (<2.5 m), the installation of PHC piles reduces the compression modulus of the soil between the piles by approximately 30%, while CMP results in a reduction of about 10%. Disturbance settlement from CMP and PHC piles accounts for approximately 3–10% and 17–28% of the total settlement, respectively. This impact diminishes with the increase of embankment load.